2016
DOI: 10.7567/jjap.55.06jg03
|View full text |Cite
|
Sign up to set email alerts
|

In situ ellipsometry of Cu surfaces immersed in benzotriazole–hydrogen peroxide solutions

Abstract: In the chemical mechanical polishing (CMP) of Cu, the Cu surface is oxidized and is concurrently removed by the mechanical function of an abrasive. Surface oxidation can lead to severe surface corrosion, and to prevent this, a corrosion inhibitor is added to slurries. Accurate understanding of the competition between oxidation and passivation is essential for advanced Cu CMP technologies. In this work, layer formation on clean Cu surfaces in benzotriazole (BTA), H2O2, and BTA–H2O2 aqueous solutions was studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Such changes in Ψ and Δ correspond to the change in the Cu surface, which involves the formation of an adsorption layer and=or oxide, as we have shown in our previous work. 23) In ellipsometry, the refractive index or thickness of the film cannot be determined from Ψ and Δ analytically. A thin film structure stacked on a substrate is modeled, its Ψ and Δ values are calculated numerically, and the numerical results are compared with the actual data to determine the film structure and optical properties of the stack.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such changes in Ψ and Δ correspond to the change in the Cu surface, which involves the formation of an adsorption layer and=or oxide, as we have shown in our previous work. 23) In ellipsometry, the refractive index or thickness of the film cannot be determined from Ψ and Δ analytically. A thin film structure stacked on a substrate is modeled, its Ψ and Δ values are calculated numerically, and the numerical results are compared with the actual data to determine the film structure and optical properties of the stack.…”
Section: Resultsmentioning
confidence: 99%
“…After the citric acid treatment, Ψ decreased to 44.41 ± 0.013 and Δ decreased to 112.09 ± 0.154 owing to the removal of the native oxide layer. 23) The specimen was then placed in an optical cell filled with 20 cm 3 of an aqueous BTA or an aqueous BTA-H 2 O 2 solution. The concentration of BTA was fixed at 0.001, 0.01, or 0.1 M. The concentration of H 2 O 2 was fixed at 0.089, 0.89, or 8.9 M; the concentrations were nominal values calculated from the reagent composition.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have studied the growth of a passivation layer on Cu in aqueous solutions of a corrosion inhibitor and an oxidizer using spectroscopic ellipsometry, [18][19][20] where benzotriazole (C 6 H 4 N 3 H, CAS 95-14-7) was used as a corrosion inhibitor and hydrogen peroxide was used as an oxidizer. Ellipsometry is a powerful tool to enable fast and real-time measurements of films on a specimen surface in a liquid and allows us to determine the physical structures and properties of the film.…”
Section: Introductionmentioning
confidence: 99%
“…BTA has been widely used for copper corrosion inhibition due to its better absorption and inhibition properties. 15,16 Similarly, adsorption of BTA and its complex formation has been investigated on cobalt surfaces and found to be better at neutral and slightly alkaline pH conditions. However, Ryu et al found that the BTA complex is not stable and can be easily removed after the DIW rinsing step.…”
mentioning
confidence: 99%